2022
DOI: 10.3390/membranes12111133
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fatty Acids (VFA) Production and Recovery from Chicken Manure Using a High-Solid Anaerobic Membrane Bioreactor (AnMBR)

Abstract: Acidogenic fermentation of chicken manure (CM) for production and recovery of volatile fatty acids (VFA) is an interesting biological waste-to-value approach compared to benchmark organic waste management strategies. Considering the wide range of high value applications of VFA, a semi-continuous immersed anaerobic membrane bioreactor (AnMBR) was applied to boost VFA productivity and yield, while reducing downstream processing stages assisting the recovery of VFA. In this regard, the effect of parameters such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This investigation revealed that the AF displays very poor VS removal when co-digested with MR, reaching values below 20%. The low VS removal could be attributed to the acidification and hydrolysis that produced VFA and the ethanol that was kept in the effluents [ 65 ]. The trend of VS removal is proportional to the methane production for both the CSTR and the AF.…”
Section: Resultsmentioning
confidence: 99%
“…This investigation revealed that the AF displays very poor VS removal when co-digested with MR, reaching values below 20%. The low VS removal could be attributed to the acidification and hydrolysis that produced VFA and the ethanol that was kept in the effluents [ 65 ]. The trend of VS removal is proportional to the methane production for both the CSTR and the AF.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic digestion effluent obtained from PPS (Abdla 2022) was collected from Östrand pulp mill (Östrand, Sweden), CKM (Yin et al 2022a) was obtained from the egg‐laying farm Sjömarkens Hönsgård AB (Borås, Sweden). VFAs were produced of both waste streams in an immersed membrane bioreactor; the separated liquid part (Abdla 2022, Yin et al 2022a) was first filtered using filter paper (Ahlstrom‐Munksjo Munktell, Thermofisher scientific) with the pore size of 10 μm, then autoclaved. The pH was adjusted to 7.1 using 1% H 2 SO 4 and 2 M NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Roughly 40 kg manure are produced per laying hen per year and 3 kg of manure per broiler (Yin et al 2022a). A common approach to treat PPS (Lin et al 2017) and/or CKM (Yin et al 2022a, Yin et al 2022b) is anaerobic digestion for biogas production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful anaerobic digestion of CM would not only be a means of manufacturing biogas in high quantity, but also a reliable source for the production of the intermediate product of anaerobic digestion called volatile fatty acids (Yin et al, 2022). Zeolite can be added to adsorb ammonia from CM leachate during anaerobic digestion to improve its biochemical methane potential (Spyridonidis et al, 2022).…”
Section: Effect Of Substrate Concentration On Specific Growth Ratementioning
confidence: 99%